2006
DOI: 10.1517/14712598.6.12.1311
|View full text |Cite
|
Sign up to set email alerts
|

Ii-Key/MHC class II epitope hybrids: a strategy that enhances MHC class II epitope loading to create more potent peptide vaccines

Abstract: Life-threatening diseases, such as cancer and pandemic influenza, demand new efforts towards effective vaccine design. Peptides represent a simple, safe and adaptable basis for vaccine development; however, the potency of peptide vaccines is insufficient in most cases for significant therapeutic efficacy. Several methods, such as Ligand Epitope Antigen Presentation System and ISCOMATRIX, have been developed to enhance the potency of peptide vaccines. One way of increasing the loading of MHC class II peptides o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 79 publications
0
30
0
Order By: Relevance
“…43 By using the Ii-Key/ HER-2/neu(776-790) peptide, a series of Ii-Key/epitope hybrids were designed and screened in vitro using peripheral blood mononuclear cells from cancer patients who had various types of HER-2-positive tumors to identify a candidate hybrid (AE37) for clinical trials. 43,45 Furthermore, CD4-positive T cells from AE37-immunized mice potentiated CD8-positive T cells to recognize and lyse autologous tumor cells more efficiently in vitro 43,45 and in vivo. [45][46][47] All of the aforementioned studies paved the way for clinical trials of AE37 in patients with breast cancer.…”
Section: Immunogenic Her-2/neu Peptides and Ii-key/her-2/neu Hybrid Pmentioning
confidence: 97%
See 4 more Smart Citations
“…43 By using the Ii-Key/ HER-2/neu(776-790) peptide, a series of Ii-Key/epitope hybrids were designed and screened in vitro using peripheral blood mononuclear cells from cancer patients who had various types of HER-2-positive tumors to identify a candidate hybrid (AE37) for clinical trials. 43,45 Furthermore, CD4-positive T cells from AE37-immunized mice potentiated CD8-positive T cells to recognize and lyse autologous tumor cells more efficiently in vitro 43,45 and in vivo. [45][46][47] All of the aforementioned studies paved the way for clinical trials of AE37 in patients with breast cancer.…”
Section: Immunogenic Her-2/neu Peptides and Ii-key/her-2/neu Hybrid Pmentioning
confidence: 97%
“…43,45 Furthermore, CD4-positive T cells from AE37-immunized mice potentiated CD8-positive T cells to recognize and lyse autologous tumor cells more efficiently in vitro 43,45 and in vivo. [45][46][47] All of the aforementioned studies paved the way for clinical trials of AE37 in patients with breast cancer. 48,49 Large Tumors Induce Strong Immunosuppression: The Concept of Vaccinating During the Early Stages of Tumor Formation It has been demonstrated that bulky tumors generate strong tolerizing conditions within their microenvironment that limit effective immunotherapy.…”
Section: Immunogenic Her-2/neu Peptides and Ii-key/her-2/neu Hybrid Pmentioning
confidence: 97%
See 3 more Smart Citations